Exogenous H2S prevents the nuclear translocation of PDC‐E1 and inhibits vascular smooth muscle cell proliferation in the diabetic state. Issue 17 (21st August 2021) - Zhang, Linxue; Jiang, Xiaoshu; Liu, Ning; Li, Mingyu; Kang, Jiaxin; Chen, Lingxue; Tang, Jingyuan; Dong, Shiyun; Lu, Fanghao; Zhang, Weihua
Abstract: Hydrogen sulphide (H2 S) inhibits vascular smooth muscle cell (VSMC) proliferation induced by hyperglycaemia and hyperlipidaemia; however, the mechanisms are unclear. Here, we observed lower H2 S levels and higher expression of the proliferation‐related proteins PCNA and cyclin D1 in db/db mouse aortae and vascular smooth muscle cells treated with 40 mmol/L glucose and 500 μmol/L palmitate, whereas exogenous H2 S decreased PCNA and cyclin D1 expression. The nuclear translocation of mitochondrial pyruvate dehydrogenase complex‐E1 (PDC‐E1) was significantly increased in VSMCs treated with high glucose and palmitate, and it increased the level of acetyl‐CoA and histone acetylation (H3K9Ac). Exogenous H2 S inhibited PDC‐E1 translocation from the mitochondria to the nucleus because PDC‐E1 was modified by S‐sulfhydration. In addition, PDC‐E1 was mutated at Cys101. Overexpression of PDC‐E1 mutated at Cys101 increased histone acetylation (H3K9Ac) and VSMC proliferation. Based on these findings, H2 S regulated PDC‐E1 S‐sulfhydration at Cys101 to prevent its translocation from the mitochondria to the nucleus and to inhibit VSMC proliferation under diabetic conditions.